Comparative analysis of mechanical behaviour of glass fiber and rice husk reinforced composites. (2022) - Haridass, R.; Jaganathan, A.; Subramani, N.; Loganathan, D.; Manikandan, N.
Abstract: This survey paper is pointed toward featuring past works of RH-filled polymer composites give data to applications and further examination in this space. Based on the information gathered, using RH-filled composites as an alternative material in aircraft and boats is extremely feasible, with their major thrusts being lightweight and low effort. However, more research into physical and synthetic treatments to strengthen the interfacial binding with the polymeric network is needed, as the fiber-polymer link is critical in determining the final composite qualities. To understand the pre-owned polymer mixes as the grid and optional fillers may influence the properties would give fascinating territories to be investigated. In this study, rice husk was mixed with glass fibers in (50 + 50) and (25 + 50) weight percentage. A glass fiber and polymer were used as binder in 25% of the mass of the fillers. A sufficient number of small specimens were produced to perform small-scale tests and assess properties such as compressive strength, thermal conductivity, dynamic stiffness, improvement in impact sound insulation, sound absorption and transmission loss. Here the data based on the rice husk and glass fiber oriented composite analysis is carried out to bring a optimized fiber reinforced polymer composites.